Comparison of ground insects diversity in cikaweni and canopy PPKA bodogol sukabumi tracks, west java - Muhammad Ilyas; Ajeng Deva Farandika; Anidya Annisa Khansa; Resma Mailantasya; Shelma Chaira; Refirman Djamahar; Rusdi Rusdi (STKIP Persada Khatulistiwa Sintang, 2023)
Nature Conservation Education Center (PPKA) Bodogol is one of the utilization zones that plays a role in preserving biodiversity. The purpose of this research was to explore the comparison of diversity and diversity index of ground insects in the Cikaweni and Canopy PPKA Bodogol, Sukabumi. The method used in this research is line transect by making a 500 m long transect line and divided into 10 plots. Each plot measures 2.5m x 2.5m, with a distance between plots of 50 m. Data processing was carried out using the Shannon-Wiener index, Eveness and similarity index. The results we got in this study found 33 individuals from 23 species of ground insects. In the Cikaweni track, the diversity value is 2.31 and the evenness index is 0.89, while in the canopy track the diversity value is 2.14 and the evenness index value is 0.93. These results indicate that both pathways belong to the moderate category without any dominating species. While the similarity index of the two tracks was 19% with only 3 species found in both tracks, namely Acheta sp., Blattella sp., and Euborellia annulipes, which means that both tracks have a low level of similarity.